2020
DOI: 10.1111/1462-2920.15331
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and biomass dynamics of unicellular marine fungi during a spring phytoplankton bloom

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 99 publications
1
34
0
Order By: Relevance
“…However, it has to be noted that marine fungal communities can be dominated by zoosporic fungi (Comeau et al, 2016). Studies from the North Sea reported temporary dominance (Priest et al, 2021) and showed, e.g., dependence on host abundance and nutrient availability (Scholz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has to be noted that marine fungal communities can be dominated by zoosporic fungi (Comeau et al, 2016). Studies from the North Sea reported temporary dominance (Priest et al, 2021) and showed, e.g., dependence on host abundance and nutrient availability (Scholz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…CalcoFluor White (CFW) staining approach along with epifluorescence microscopy, as suggested by Rasconi et al (2009), was used to detect and identify fungal parasites attached to an algal hosts. CFW is a non-specific, fluorescent dye that binds to chitin in fungal cell walls but also cellulose, that is often present in cell wall of some algae and fungi-like organisms (Kagami et al, 2007;Priest et al, 2021). Pre-treatment of sediment samples was done using ultrasound (3 × 10 s) for the mechanical disruption of diatom-sand agglomerates (Scholz et al, 2014).…”
Section: Microscopymentioning
confidence: 99%
“…Fungi are ubiquitous in the ocean [ 12 ] and have been isolated from marine habitats including mangrove leaf litter, seagrass, seaweed, subseafloor sediments, and hydrothermal vents [ 13 – 17 ]. Mycoplankton are fungi that live in seawater that tend to correlate with phytoplankton [ 18 – 20 ] and are hypothesized to be an important component for carbon cycling and within marine food webs [ 10 , 11 ]. Notably, mycoplankton were recently found to dominate total biomass on marine snow [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we used 13 C DNA stable isotope probing (SIP) to track fungal carbon assimilation of particulate 13 C-labeled diatom extracellular polymeric substances ( 13 C-dEPS) in the water column and sediments underlying the Benguela Upwelling System (BUS) of Namibia. We used 13 C-dEPS as a tracer for fungal marine organic matter assimilation because diatom derived polysaccharides are major contributors to the marine carbon cycle [ 22 , 23 ], fungi can dominate total biomass on marine snow [ 21 ], and marine fungi are often associated with diatom blooms [ 18 , 19 , 24 ]. The BUS is one of the most productive ecosystems of the world’s oceans [ 25 ] and represents a nutrient-rich habitat where the saprotrophic traits of fungi are hypothesized to be important [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%